The readiness of knowledge managament implementation at pt security training - Dwi Oktari, Putri; Bekti, Rudy (The Indonesian Journal of Business Administration, 2019)
Abstract - PT SECURITY TRAINING is one of the Security Services Business (BUJP). As a newcomer company in this industry, PT SECURITY TRAINING must be able to continue to grow and improve its competence and performance to compete with other companies. Lack of knowledge management causes several problems. Due to poor KM, the potential of losing knowledge that must be used, stored and distributed to support business operations. This study is focused on knowing the readiness of PT SECURITY TRAINING to implement knowledge management in order to get a better performance. Using knowledge management maturity assessment by adopting elements of APO KM Framework, researcher found that the maturity of knowledge management implementation of PT SECURITY TRAINING is at level initiation, which means that the company is starting to recognize the need to manage knowledge or may have started a knowledge management pilot project. Based on the results of this study it can be concluded that there are several obstacles that come from several elements such as processes, human resources, technology, and governance. The recommendations are to develop a business strategy, creating a KM team/division, developing a KM strategy, pilot testing and deployment, develop a KM evaluation system, implement KM, also give do some evaluation and give rewards.Keywords: Organizational Readiness, Knowledge Management Implementation, KM Strategy